Challenges in the Field of Whistleblower Personal Data Protection in Polish Law Compared to European Solutions - Bielak-Jomaa, Edyta (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
In this chapter, the author presents the problem of the protection of whistleblowers’ personal data in the workplace in connection with the processing of their data in the channels for reporting breaches in the context of the transposition of the Directive on the protection of persons who report breaches of Union law into Polish law. The existing regulations ensure limited protection for employees and other individuals against retaliation or violation of privacy. The author postulates the necessity to develop comprehensive whistleblower legislation. The purpose of the legislation will be to oblige the employer to develop and implement solutions that will guarantee genuine confidentiality and protection of whistleblowers’ personal data.